Aerosol Dispersion Model of Instant Release of the Active Substance - Оlexandr Lavnichenko, Vladimir Batsamut, Serhii Hodlevskyi, Yurii Babkov (International Journal of Advanced Science and Technology, 2019)
In the article, based on the analysis of known works, an aerosol dispersion model study was conducted, which most adequately describes expanding of an aerosol cloud formed because of the use of a of tear gas riot control means. A detailed description of the content of the model is provided. The results of simulation and experimental studies that were conducted to verify the adequacy and accuracy of the model of "heavy gas" are presented. The estimates of the model accuracy are given.